Reflexões sobre uma crítica de dança: o Balé da cidade de São Paulo na visão dos cadernos culturais da Folha de S. Paulo e de O Estado de S. Paulo - Benvegnu, Marcela (2007)
The goal of the current research is to understand the various forms given to the Balé da Cidade de São Paulo's (BCSP) - Companhia 1 - of Theatro Municipal de São Paulo (TMSP), through specialized dance critics. It is meant to describe, analyse and compare this material to underline it concepts and how it is presented in the brazilian contemporary critical. The selected corpus is from two important newspaper available in the entire country: Folha de S. Paulo and O Estado de S. Paulo, from 2001 to 2006. The research is based in a collection of pieces about the Balé da Cidade de São Paulo produced in this period. This collection will have the critical analysed and assessed in its concept and in the role of connecting people and artwork. Also, this connection could be classified as critical act comunication dimension as wrote Jacques Leendhard. For Baudelaire, the critical must be partial, passionate and political. This study also tries to introduce the critical concept, considering the time that it was written, the concepts introduced by the critics in the publication, the point of view and the freedom of analyse, which many experts claims that is the reason of the critical to have the role of inform and create opinion. According to Graham McFee, the dance's critical that is presented in newspapers has a deeper meaning and the words must be transformed in motion. As result, it is expected that this research will be able to reveal the importancy of BCSP in TMSP and of its pieces path; reflect about the role and dance's critical quality produced in the brazilian's media; understand better the point of view of each newspaper and the role and thoughts of various dance critics